Development of educational video feeding practice for children with cerebral palsy - Desita Ike Sagita; Harsono Salimo; Tri Rejeki Andayani (AcTion: Aceh Nutrition Journal, 2023)
Feeding practice videos containing nutritional content for caregivers of children with cerebral palsy (CP) are often found in English. This study aimed to develop an educational video of feeding practices for children with CP that is feasible in Indonesia to improve the nutritional knowledge and skills of caregivers regarding feeding and drinking. The Research and Development method was used with the ADDIE model, which consisted of analysis, design, development, implementation, and evaluation stages. Small-group and field-group trials were conducted at the PNTC, IFA, and YPAC Surakarta pediatric physiotherapy clinics from February to April 2023. Video validation was performed by three experts: nutritionists, physiotherapists, and media experts who were competent in their fields. The video results based on nutritionist validation were 76,4%, physiotherapist validation results were 85,5%, and 82,4% media expert validation results. These results indicate that the video feeding practice developed as an educational media is suitable for use with minor improvements, according to expert advice. The trial results for the small group comprised ten respondents and obtained highly feasible results (90,3%). A field trial with 15 respondents obtained a result of 89,7% in the feasible category. In conclusion, an educational video of feeding practices for caregivers of children with cerebral palsy is feasible.